Thermo-analytical study of a melt cast composition based on cis-1,3,4,6-tetranitrooctahydroimidazo-[4,5 d]imidazole (BCHMX)/trinitrotoluene - Hussein, Ahmed Khaled Mohamed; Elbeih, Ahmed Ikhlas Mohamed; Zeman, Svatopluk (My University, 2018)
The thermal behavior and decomposition kinetics of a melt cast composition based on mixture of bicyclic nitramine, cis-1,3,4,6-tetranitrooctahydroimidazo-[4,5-d]imidazole (BCHMX) and insensitive explosive, 2,4,6-trinitrotoluene (TNT) (60/40 by wt %) have been investigated. This behavior was studied by non-isothermal TG and DSC techniques and the decomposition kinetics were determined by the isoconversional methods named Kissinger and modified Kissinger-Akahira-Sunose (KAS). For comparison, the traditional TNT casted compositions based on 1,3,5-trinitro-1,3,5-triazinane (RDX) named composition B and β-1,3,5,7-tetranitro-1,3,5,7-tetrazocane (β-HMX) were studied. Also Vacuum Stability Test (VST) was used isothermally at 120 °C for six hours to determine the specific rate constants. Despite of the volatility of TNT, the obtained results showed that the reactivity of the studied cyclic nitramines in mixtures was increased in the order HMX < BCHMX < RDX, because of their incorporation into the melted TNT (acidic solvent). The kinetic compensation effect and outputs of the Vacuum Stability Test clearly exemplify this reactivity. Nevertheless, taking into consideration the recently published facts about this composition and its application in practice, the mixture is a promising composition which has high relative explosive strength compared with the other studied compositions.
Thermo-analytická studie litelné kompoziceí na bázi cis-1,3,4,6 - tetranitrooctahydroimidazo-[4,5 d] imidazol (BCHMX) a trinitrotoluenu v porovníní s tradičními kompozicemi. Thermo-analytická studie litelné kompoziceí na bázi cis-1,3,4,6 - tetranitrooctahydroimidazo-[4,5 d] imidazol (BCHMX) a trinitrotoluenu v porovníní s tradičními kompozicemi. Thermo-analytická studie litelné kompoziceí na bázi cis-1,3,4,6 - tetranitrooctahydroimidazo-[4,5 d] imidazol (BCHMX) a trinitrotoluenu v porovníní s tradičními kompozicemi.
Keywords: TNT; Nitramines; Thermal decomposition kinetics; Compensation effect; TNT; Nitraminy; Kinetika tepelného rozkladu; Kompenzační efekt